Thinopyrum species as a genetic resource: enhancing salt tolerance in wheat and forage crops for sustainable agriculture - Li, Wei; Li, Hongwei; Zheng, Qi (Frontiers in Plant Science, 2025)
Thinopyrum species are native to coastal regions and have evolved notable salt tolerance mechanisms, including efficient Na+ exclusion and K+ retention, enhanced antioxidant capacity, and the accumulation of compatible solutes for osmoregulation. Among the Thinopyrum species, Th. ponticum has long been used as saline pasture and energy plant, which was recently suggested for the construction of a “Coastal Grass Belt” around the Bohai Sea. The salt tolerance in some Thinopyrum species, such as Th. ponticum, Th. elongatum, Th. bessarabicum, and Th. distichum have been transferred into wheat as (partial) amphiploid, addition, substitution, translocation, and introgression lines. The introgression lines with enhanced salt tolerance, derived from wheat × Th. ponticum had been utilized as salt-tolerant wheat varieties. In addition, amphiploids and perennial wheat have been developed as salt-tolerant forage crops. Salt tolerance in Thinopyrum species is governed by multiple genes, which have been mapped principally to homologous chromosomes group 3 and group 5. Transcriptomic and proteomic analyses have revealed a number of differentially expressed genes (proteins) involved in the salt tolerance response in Thinopyrum species; however, few of these have been functionally characterized. Therefore, further work is needed to investigate gene networks underlying salt tolerance in Thinopyrum, which may serve as molecular targets for the genetic improvement of salt-tolerant forage crops such as Tritipyrum and staple crops like wheat.